2019
DOI: 10.1017/dmp.2019.46
|View full text |Cite
|
Sign up to set email alerts
|

Core Capacities for Public Health Emergencies of International Concern at Ground Crossings: A Case Study from North India

Abstract: Objective:International airports, ports, and ground crossings are required to have health units for undertaking public health measures during routine times and specific measures during the time of public health emergency of international concern (PHEIC). This study was conducted at a ground crossing of North India to assess the implementation status of International Health Regulations (IHR) (2005) at a ground crossing in the prevention and control of public health emergencies and to assess the risk of imported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Our findings shown that significant improvement is required to acquire the IHR routine capacities at POEs while in India, they were fairly consistent with IHR requirements at ground crossings(83%) [ 13 ]. Access to medical care at POEs, especially airports is generally provided.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Our findings shown that significant improvement is required to acquire the IHR routine capacities at POEs while in India, they were fairly consistent with IHR requirements at ground crossings(83%) [ 13 ]. Access to medical care at POEs, especially airports is generally provided.…”
Section: Discussionsupporting
confidence: 69%
“…We found that overall, the POEs assessed in Cameroon need significant improvement (score below 50%) to fulfill the IHR requirements. Cameroun POE therefore has longer way to go compared to other developing countries such as Uruguay [ 12 ] and India [ 13 ] where IHR capacities need just few improvements to meet IHR standards. This poor performance of POEs in Cameroon can be attributed to the unilateral designation of the POEs by the Ministry of Public Health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations